Examination of droughtmaster bulls for breeding soundness - Bongso, T. A.; Jainudeen, Mohamed Razeen; Dass, S (Elsevier, 1981)
Forty Droughtmaster bulls were evaluated for breeding soundness, using the method of examination and criteria for classifying bulls of the Society for Theriogenelogy. Eighty three percent of the bulls were classified as satisfactory, 14 percent as questionable and 3 percent as unsatisfactory breeders. Scrotal circumference for 2 to 8-year-old bulls were smaller in questionable and unsatisfactory bulls, as compared to satisfactory bulls. For bulls rated as satisfactory breeders, the scrotal circumference of 37 to 43 cms was higher than for other beef breeds. Three related bulls (2 questionable, 1 satisfactory) carried sperm defects classified as 'knobbed' (38 +/- 3%), 'Dag' (40 +/- 4%) and 'pseudo-droplets' (41 +/- 5%), which may adversely affect fertility.